2013
DOI: 10.1063/1.4788982
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction and extended X-ray absorption fine structure study of epitaxial mixed ternary bixbyite PrxY2−xO3 (x = 0–2) films on Si (111)

Abstract: Ternary single crystalline bixbyite PrxY2−xO3 films over the full stoichiometry range (x = 0–2) have been epitaxially grown on Si (111) with tailored electronic and crystallographic structure. In this work, we present a detailed study of their local atomic environment by extended X-ray absorption fine structure at both Y K and Pr LIII edges, in combination with complementary high resolution x-ray diffraction measurements. The local structure exhibits systematic variations as a function of the film composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…For example, we have found a bimodal distribution of cation-oxygen bond lengths in mixed (Pr,Y) 2 O 3 system. 30 Similar behavior induced by lattice distortion and disorder has also been reported in other oxide 71 or semiconductor 72,73 alloy systems.…”
Section: E Discussionsupporting
confidence: 50%
“…For example, we have found a bimodal distribution of cation-oxygen bond lengths in mixed (Pr,Y) 2 O 3 system. 30 Similar behavior induced by lattice distortion and disorder has also been reported in other oxide 71 or semiconductor 72,73 alloy systems.…”
Section: E Discussionsupporting
confidence: 50%
“…While CeO 2 adopts a cubic fluorite structure ( Fm 3̅ m ) with Ce showing a +4 valence state, its neighboring RE oxide praseodymium oxide, which has a complex phase diagram, shows a clear preference for the Pr 3+ valence state either in the form of a cubic bixbyite ( Ia 3̅) or hexagonal ( P 3̅ m 1) structure. Bixbyite can be considered as an intrinsic oxygen deficient fluorite in which the lattice parameter is doubled by removing in a systematic way a quarter of the oxygen atoms. , We will show that real mixed Ce 1– x Pr x O 2−δ ( x = 0–1) solid solution films have been obtained and doping Pr 3+ into CeO 2 lattice can effectively create Vo ·· in CeO 2 films. It will also be demonstrated that FM properties dramatically depend on the Pr-doping level (thus relative Vo ·· concentration) in the films.…”
Section: Introductionmentioning
confidence: 88%
“…Access to the low temperature bixbyite (C) phases permits the investigation of the high temperature phase transitions to the trigonal (A) and monoclinic (B) phases. The Y x Pr 2– x O 3 solid solution has been reported as fully reduced cubic bixbyites (C) in thin films synthesized by molecular beam epitaxy, and bulk samples which were made via a sol–gel method . Furthermore, the bulk samples studied by Lussier et al explored the oxidation of the bixbyite starting materials to fluorites.…”
Section: Introductionmentioning
confidence: 99%